Sand Solidification through Microbially Induced Carbonate Precipitation for Erosion Control: Prospects in Bangladesh (Journal of Environmental Science and Natural Resources, 2016)
Bio-cementation is a sand consolidation technology, in which ureolytic bacteria release carbonate from urea hydrolysis in the presence of an excess of calcium ions to form calcite (CaCO3) in-situ. Biocementation is to enhance the strength and stiffness properties of soil and rocks though microbial activity or products. This paper addressed the prospect of microbial carbonate precipitation for erosion control in Bangladesh. Bacterial CaCO3 precipitation under appropriate conditions is a general phenomenon where the ureolytic bacteria uses urea as an energy source and produces ammonia which increases the pH in the environment and generates carbonate, causing Ca2+ and CO32- to be precipitated as CaCO3. This CaCO3 join sand particles and forms rocklike materials that auto-repairs by means of sunlight, seawater, and bacteria as microbially induced carbonate precipitation method. These rock particles when produced artificially is called artificial rock and has the potentiality to protect coastlines from erosion.J. Environ. Sci. & Natural Resources, 9(1): 59-61 2016